Analysis of smart governance in tax digitalization in Bandung city (a case study of e-Satria application) - Adisa, Regina Fauzia; Mulyani, Sri (Universitas Padjadjaran, 2025)
This study aims to analyze the implementation of the e-Satria application in achieving smart governance in the city of Bandung. The analysis includes community participation, transparency, and quality of service as evaluated through effectiveness, efficiency, time savings, and data security. This study employs a qualitative approach. The validation of research data utilizes data triangulation, where information is gathered from various informants, documents, and an analysis of the e-satria application. The informants for this study included representatives from the Regional Revenue Management Agency (BPPD), the Bandung City Inspectorate, and De.U Coffee, a restaurant in the Bandung area that uses the application. Data analysis consisted of data reduction, presentation, and conclusion drawing. The study's findings indicate the successful implementation of tax digitalization via the e-satria application. This application meets the criteria for smart governance, namely community participation, transparency, and improved service quality, which are reflected in effectiveness, efficiency, and service time. However, a clearer implementation policy is still necessary to maximize its effectiveness.